Self-assembled monolayer-based immunoassays for okadaic acid detection in seawater as monitoring tools. (February 2018) - Leonardo, Sandra; Toldrà, Anna; Rambla-Alegre, Maria; Fernández-Tejedor, Margarita; Andree, Karl B.; Ferreres, Laura; Campbell, Katrina; Elliott, Christopher T.; O'Sullivan, Ciara K.; Pazos, Yolanda; Diogène, Jorge; Campàs, Mònica
Abstract: Rapid and cost-effective methods to monitor the presence of diarrhetic shellfish poisoning (DSP) toxins in seawater samples in an easy and reliable manner are required to protect human health and avoid economic losses to shellfish industry. Immunoassays for the detection of okadaic acid (OA) and dinophysistoxin-1 and dinophysistoxin-2 are developed by immobilising OA on self-assembled monothiols or dithiols in an ordered and oriented way, providing an effective limit of detection of ∼1 ng OA equiv./mL seawater. The immunoassays are applied to the analysis of the particulate fraction of seawater samples from two Catalan harbours (NW Mediterranean) and samples collected periodically from the Galician Rias (E Atlantic), as well as a reference mussel sample. Results are in agreement with LC-MS/MS and the certified values. OA concentration in seawater correlates with Dinophysis cell abundance, with a 1–2 weeks lag. The immunoassays provide powerful high-throughput analytical methods potentially applicable as alternative monitoring tools. Graphical abstract: Highlights: Okadaic acid (OA) is immobilised on self-assembled monothiols and dithiols. OA content from multiple seawater samples from different locations is determined. The correlation between Dinophysis cells and OA content in seawater is evaluated. A mussel containing OA, DTX-1 and DTX-2 certified contents is successfully analysed. Good correlations between immunoassays, LC-MS/MS and certified values are obtained.